A squeeze on spending? An update on household living costs for senior Australians - Kelly, Simon (National Seniors Productive Ageing Centre, 2013)
A 2011 NSPAC research report into the costs of living found that water, electricity, gas, medical services and rent had all risen at more than double the inflation rate over the previous five years. This report follows up on that previous report by updating the price increases and examining their impact on the spending patterns of Australia’s 2.9 million senior households. It focuses on findings for three senior age groups: households aged 75 years and over (75+ households), households aged 65–74 years, and households aged 50–64 years.
Keywords: Ageing -- Retirement; Income & Finance; Benefits and Payments; Income, wealth and finances; Ageing; Income & Finance; Benefits and Payments; Ageing; Retirement; Ageing; Income, wealth and finances